Dampak Penggunaan Aplikasi ATLAS terhadap Audit Persediaan yang Optimal di Era Digital (Jurnal Kendali Akuntansi, 2025)
The advancement of information technology has significantly transformed modern audit practices, particularly in inventory audits. This study aims to analyze the impact of the Audit Tools and Linked Archive Sistem (ATLAS) application on the effectiveness and efficiency of inventory audits in the digital era. A qualitative approach was employed through observation and interviews with auditors who utilize ATLAS in their audit procedures. The findings indicate that ATLAS improves audit speed, enhances documentation, and supports the accuracy and transparency of financial reporting. Despite challenges such as limited client system integration and auditor adaptation, internal training and data digitization strategies prove to be effective solutions. Thus, ATLAS serves not only as a documentation tool but also as a system that strengthens the overall quality and accountability of inventory audits.